PELATIHAN TATA RIAS DAN BUSANA UNTUK GURU DAN SISWA TK NASYIATUL AISYIYAH MUNGKA, KEC. MUNGKA, KAB. 50 KOTA - Maryelliwati Maryelliwati (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2019)
Providing cosmetology and fashion training for teachers and TK Nasyatul Aisyiyah  students is a form of Higher Education Tri Dharma conducted. Makeup and fashion training is a form of training that is useful for teachers to provide methods of dressing and dressing both in everyday life, beautiful and stout, and so forth. Whereas for students is to describe or introduce how to dress and make up that is good and reasonable. The expected outcome of this dedication is that teachers and students are able to teach and understand and understand what kind of dressing and good dress is.